(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Objectives: This study aimed to investigate the psychological impact, specifically depression, anxiety, and self-directed violence, in women suffering from endometriosis. Study design: A cross-sectional study. Place and duration of Study: Department Of Psychiatry & Gynae & Obs Mardan Medical Complex (MMC) Mardan, From 05-January 2021 To 05-July 2021. Methods and Materials: Out of Eighty women, aged 20-50 and residents of Mardan, participated. Psychological distress was measured using the Patient Health Questionnaire (PHQ-9) for depression, the Generalized Anxiety Disorder Scale (GAD-7) for anxiety, the Body Appreciation Scale-2 (BAS-2) for self-acceptance, and the Depressive Experiences Questionnaire (DEQ) for self-criticism. Statistical analyses included descriptive statistics, the Kruskal-Wallis test, one-way ANOVA, chi-square tests, and correlation analyses. Results: Women with endometriosis had significantly higher levels of depression and anxiety compared to healthy participants. Those with additional chronic illnesses (endometriosis ACI) exhibited the highest levels of depression and anxiety, as well as lower body image and higher self-criticism. Significant correlations were found between pain levels and psychological distress, with higher pain scores associated with increased depression and anxiety. Conclusion: The study highlights the profound psychological impact of endometriosis, emphasizing the need for an interdisciplinary approach to treatment. Raising awareness, ensuring timely diagnosis, and providing comprehensive care are crucial in mitigating the mental health consequences of endometriosis.